Anemia in Malagasy hospitalized patients - Nirina, Marie Ose Michael Harioly; Rasolonjatovo, Anjaramalala Sitraka; Nirina, Marie Osé Judicael Harioly; Andriamamonjisoa, Sitraka Stella; Rasamoelina, Andrindrantosoa; Rakoto Alson, Aimée Olivat; Rasamindrakotroka, Andry (International Journal of Research in Medical Sciences, 2021)
Background: Anemia is a public health problem with major health consequences. According to the WHO, anemia worldwide is 1.62 billion people (95% confidence interval (CI): 1.50-1.74 billion), which corresponds to 24.8% Of the population (95% CI: 22.9-26.7%). Methods: We studied the clinical and biological data of hospitalized patients who applied for a complete blood count in hematology laboratory of Joseph Ravoahangy Andrianavalona Antananarivo hospital between January and April 2017. Results: Sixty-four percent of hospitalized patients had anemia. Anemia was more common in women. Anemia was encountered mainly in intensive care unit (33.9%) and occurred in perioperative cases in the majority of cases (33.4%). Conclusions: Anemia is a common symptom in hospitals, particularly in intensive care unit. In the Malagasy hospital environment, etiologies are numerous, in particular hemorrhage, sickle cell disease or cancer.